Онтоморфогенез і сезонний розвиток Veltheimia bracteata Harv. (Hyacinthaceae Batsch) - Zhila, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of ontomorphogenetic study of Veltheimia bracteata Harv. on the periods of ontogenesis and seasons are given. Indicator characters of the age conditions of individuals are brought.